How to develop spiritual awareness in the organization. Issue 8 (2nd September 2014) - Sirodom, Kulpatra; R. Loza Adaui, Cristian; Habisch, André; Lenssen, Gilbert; Roosevelt Malloch, Theodore; Shah, Snehal; Sachdev, Anil
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to propose a theoretical model that leverages the practical wisdom of the Panch-Kosa framework of yogic philosophy to develop an awareness of spirituality in the organization. It also provides quasi-quantitative empirical evidence to demonstrate its potential application. Design/methodology/approach – A survey was designed and administered in four different organizations. Correlation, ANOVA and χ2 analysis were conducted to explore the applicability of the proposed framework. Findings – The results indicate that values, as reflected in the physical aspects of an organization such as its logo, symbols and organizational elements characterized as "practice of Fair Governance" and "HR Effectiveness", influence employee-related outcomes. Further, the study found that when there is a perfect "alignment" between an organization's intent to honor values and its corresponding actions, employees perceive the highest levels of holistic engagement. Research limitations/implications – This study has an implication on how to leverage practical wisdom from Hindu philosophy to enable individuals and organizations to transform to a higher level of consciousness. Originality/value – The paper has ventured into an uncharted territory of integrating the yogic framework of Panch-Kosa to the organizational elements and has provided preliminary support for its applicability in organizations. Moreover, it operationalizes the notion of alignment between organization's value-centric strategy and actions and its impact on employee-related outcomes.